Desain LKPD Pendekatan Saintifik Dengan Permainan Teka-Teki Silang Barisan dan Deret - Sormin, Masdelima Azizah; Harahap, Kholid Umar; Angraini, Widya Diningrat Sri; Harahap, Amir Solihin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop Learner Worksheets (LKPD) based on a scientific approach with crossword puzzles on the material of rows and series for class VIII students of SMP Negeri 1 Sipirok. The research used the Research and Development (R&D) method with the subject of class VIII students. The validity test was carried out by three validators consisting of two Mathematics Education lecturers and one junior high school mathematics teacher. The instrument used was a validation questionnaire which included three aspects, namely material, media, and language. Material validation assesses the suitability of LKPD content with the material and approach used, media validation assesses the display component and images, while language validation assesses the suitability of language with EYD rules. The validation results showed a percentage of 87.5% for material aspects, 93.75% for media aspects, and 82.5% for language aspects, all of which were in the “Very Valid” category. Overall, the validity level of the LKPD reached 87.92% (Very Valid), so it was declared feasible to use as teaching material. Overall, the validity level of the LKPD reached 87.92% (Very Valid), so it was declared feasible to use as teaching material. The practicality test was conducted through a questionnaire to students to find out the ease of use of the LKPD. The results showed a percentage of 79.65% with the category “Practical”, which means that the LKPD is easy to use in the learning process. This finding shows that the LKPD based on a scientific approach with a crossword puzzle game on the material of rows and series can increase student involvement and understanding of the material of rows and series.